Analisis Faktor – Faktor Yang Mempengaruhi TPAK Aceh Dalam Jangka Panjang Dan Jangka Pendek - Fajar Aulia Ramadhan; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2023)
This study aims to determine the relationship between the provincial minimum wage, average length of schooling, inflation, population and labor force participation rate in Aceh Province in 2006 – 2020. This research uses secondary data for 15 years. This study used the Autoregressive Distributed Lag (ARDL) test analysis method. The results of this study show that in short-term testing the provincial minimum wage variables, average length of schooling, and population have a positive but not significant effect on the labor force participation rate and the inflation variable has a negative but not significant effect on the labor force participation rate. Meanwhile, in the long term, the provincial minimum wage, average length of schooling, and population have a positive but not significant effect on the labor force participation rate and the inflation variable has a negative but not significant effect on the labor force participation rate